(3CYdGe GdOjf aj UaGJ GdeDefjf hcfR GdYGQajfs - (3eMeO Hf GdMSf GdOjdej,J (B711 (3g` s ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GdMSf Hf CHj GdMSf GdOjdej Efj MjK oHdjJ HOGA GdZQhQ habOJ GdCfjS GdUGdM aj GdhMTI hMedfj eYQaI GdfGS Ydi GdhMOI s
(3BNQgG (B:s
(3Gddge CUdM VejQ hGYa Yf JbUjQ hCcJHfj ef GdaGFRjf hGdMeO ddg QH GdYGdejf hUdhGJg Ydi eMeO GdfHj GdCejf JeJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B190s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(630) s
Keywords: (3GdJhMjO hGdedd hGdfMds